Two new species of the genus Luzonomyza from CHINA (Diptera, Lauxaniidae) - Shi, Li; Yang, Ding (Zootaxa, 2015)
Two species Luzonomyza gaimarii sp. nov. and Luzonomyza hirsuta sp. nov. are described as new to science. A key to separate species of the genus is provided.